With Munari the Form of the Book Followed its Function - Santos, Tiago José Miranda (2018)
Munari's Books by Giogio Maffei, like its subtitles states, is “the definitive collection of book designs by Bruno Munari”, being “the first English-English monograph” about him. Bruno Mu-nari was an Italian designer who lived between 1907 and 1998, and made a huge contribution to an understanding of the materialities of the book and its interdisciplinary functionality as we know it nowadays. He considered books the “best medium to communicate his visual ideas (...) and convey his crea-tive spirit” and by his practices he created new perspectives about the possi-bilities inherent in bibliographic structures as forms of visual and haptic communication.